STRATEGY FOR IMPLEMENTING CORPORATE SOCIAL RESPONSIBILITY (CSR) IN THE BATANG INTEGRATED INDUSTRIAL AREA: REALISING SUSTAINABLE DEVELOPMENT THROUGH ECONOMIC EMPOWERMENT OF LOCAL COMMUNITIES: UIN K.H ABDURRAHMAN WAHID PEKALONGAN - Pramono, Sigit; Rasa Putra, Augasta Eka; Shulthoni, Muhammad (PT. Media Edutama Nusantara, 2024)
This study aims to explore the implementation of Corporate Social Responsibility (CSR) programs carried out by the Batang Integrated Industrial Estate (KITB) in empowering the local community economy in three sub-districts around the industrial area. The main focus of this study is to analyze the impact of CSR programs such as competency-based work skills training, Mandarin language training, and support for MSMEs on local economic development. The research method used is a qualitative approach with a descriptive method, which involves collecting primary data through interviews with informants from various related parties and secondary data from literature studies and documentation. The results of the study indicate that the KITB CSR program has succeeded in improving the competence of the local workforce and expanding economic opportunities through various initiatives, such as skills training and MSME empowerment. The Mandarin language training program has also proven effective in improving the competitiveness of local communities in communicating with investors from China. However, challenges related to low community participation, cross-sector coordination, and program sustainability still need to be addressed. In conclusion, the KITB CSR program has made a significant contribution to the economic empowerment of local communities, but it needs improvement in terms of coordination and sustainability to achieve more optimal results.